Kilka uwag o sposobach rozstrzygania sporów dotyczących sprawczego współdziałania w popełnieniu przestępstwa indywidualnego - Kardas, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The following research paper is devoted to the analysis of the issue of criminal liability of the extraneus for agential cooperation in committing an individual crime. It sets out to describe the historical concept of the extraneus’ responsibility for his cooperation in committing an individual crime and to further evaluate the fundamental theoretical, criminal, political and dogmatic problems associated with the above mentioned matter.When it comes both to the criminal and political aspects, our analysis focuses on how to justify grounds for criminal liability in cases where the perpetrator of an individual cooperative crime does not fulfi ll the statutory requirements which must be met so as to constitute such an offense.As for the theoretical aspect, it depicts the possible models of solving the extraneous’ liability issue by juxtaposing two mutually exclusive conceptions. First of these is based on the modification of the elements of an individual offense, thus transforming it into a crime that can be perpetrated by any offender ordinary crime? in case of agential cooperation. The second one, however, advocates including new elements into the criminal code, the actualization of which will constitute grounds for accepting the extraneus’ liability for cooperation in committing an individual crime without modifying the statutory characteristics of the agential subject.Finally, the dogmatic insights review the current regulations and provisions.To sum up, it is proposed to order the statutory regulations by using and implementing one of the aforementioned theories.
Keywords: prawo karne; przestępstwo indywidualne; wspóludział w przestępstwie; współpraca przy popełnieniu przestępstwa; odpowiedzialność karna